Pengembangan Rapor Berbasis Microsoft Access Untuk Guru SMK - Zarlaini Zarlaini; Hary Soedarto Harjono; Akhmad Habibi (Universitas Negeri Padang, 2023)
The background of this research is that it is very difficult for teachers or homeroom teachers to actualize their abilities in filling out report cards every semester.Filling in manually from typing one by one using Microsoft Word makes all teachers or homeroom teachers bored with this situation.The product of the author is a simple report card. Therefore, it is no longer difficult for teachers to fill out report cards so that in the future filling out report cards will no longer make teachers tired.This development research aims to produce a simple report card product.This research was conducted at SMK Negeri 2 Sarolangun.The learning multimedia model used in this study is Lee & Owens (2004).The development stages passed are: Analysis, Design, Development, Implementation and Evaluation.The resulting product is in the form of a report card which was developed using Microsoft Access and later can be accessed on each teacher's laptop.The feasibility test was carried out by media experts, and the assessment by the teacher.The results of the research based on the feasibility test of the media are suitable for use by end users in the very good or very feasible categories.The criteria are reflected in the aspects that have been assessed, namely, presentation, method of use, media for users, namely teachers, ease of use of the product, received a very good rating category.The results of the field trials show the enthusiasm of the homeroom teacher in using the report cards that the author has done during individual trials and limited trials.They seemed happy with this product even though it was not as perfect as imagined, but they were no longer tired of typing one by one.Based on the results of data analysis, it shows that the quality of the report card application development product is very good.Thus it can be suggested, that the media can be used as a very simple application in filling out report cards.This product still needs to be developed with a better appearance so that it can be used by other SMK.